Seaweed growth promoter can boost up the crop growth and enhance the economic yield of irrigated wheat - BHAWESH, BHANU; KUMAR, BINOD; MANDAL, NINTU; GHOSH, MAINAK; SHARMA, ALKAJYOTI (Journal of Soil and Water Conservation, 2023)
Plant biostimulants, a versatile product, helps to resolve many issues of contemporary crop production. The present investigation was conducted in the experimental farm of BAC, Sabour, Bhagalpur during rabi season of the year 2021-2022. The experiment was laid out in Randomized Block Design with ten treatments replicated thrice. The IFFCO based seaweed extract “Sagarika” was used in this experiment as soil application (5, 10 and 20 kg/acre) during final land preparation along with recommended dose of fertilizer (RDF). The product “Sagarika” was also applied as foliar (2.5, 5.0 and 7.5 ml/L) at 45 and 65 days after sowing (DAS) with RDF. The RDF was applied as full dose of P2O5 and K2O with 1/3rd dose of N as basal followed by two equal splits of N was made at 25 and 45 DAS. The growth attributes like plant height, leaf area index and tillers number at initial days (25 to 45 DAS) were observed significantly highest against the application of “Sagarika” @ 20 kg/acre with 100% RDF. However, during the later stages (65 to 105 DAS) impact of soil and foliar application recorded significantly superior growth attributes over 100% RDF. The medium and higher doses of soil applied seaweed extract (Sagarika) as in T4 and T5 performed better yield attributing characters over the foliar treated plots. The soil application of “Sagarika” recorded 14.1%, 11.7% higher grain and straw yield, respectively over the 100% RDF. The maximum amount of available soil nitrogen (217 kg ha-1) was measured under basal application of “Sagarika” @ 20 kg acre-1 with 100% RDF. Therefore, the seaweed growth promoter “Sagarika” benefitted crop growth, productivity and soil nitrogen status when incorporated with RDF at medium and higher doses combining as soil/foliar or both.